EXECUTION OF FIDUCIARY GUARANTEE UNDER LAW NO. 42 OF 1999 ON FIDUCIARY GUARANTEE (A SOCIO-JURIDICAL ANALYSIS TO ANTICIPATE ITS EFFECTIVENESS) - Hutagalung, Arie S. (UI Scholars Hub, 2013)
Fiduciary Guarantee (Fiduciary Law) which approved by the House of Representatives of the Republic of Indonesia (DPR RI) on September 9, 1999 has accommodate the public needs to help business activities and to provide legal certainty to the interested parties. With the increase in the development activities and the needs for funding, a majority of funds are needed to meet the lending and borrowing activities that require protection for the lender and the borrower through a guarantee institution that can provide legal certainty and protection to the lender or the borrower. Viewed from the current lending practices, there is a difficulty on the part of the Fiduciary Guarantee to conduct the fiduciary execution if the Fiduciary Grantor defaults since in fact the goods being a fiduciary object are still in the possession of the Fiduciary Grantor or Debtor, then in line with the provisions of article 1977 of the Indonesian Civil Code, known as the principle of bezit geldt als volkomen titel.